The Impact Of Climate Change On Global Shipping Pathways In 2025 - Hendrin Agus Franciscus Hia; Panji Suwarno; Widodo Widodo; Herlina Juni Risma Saragih; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Climate change has emerged as a pressing global issue, significantly impacting various aspects of human life and the environment. In the context of the shipping industry, a crucial pillar of international trade, the effects of climate change are both direct and profound. By 2025, the repercussions of climate change are expected to become increasingly evident, with rising sea levels, predicted to reach between 0.3 to 1 meter by the end of the century, altering existing port topographies and shipping routes. The frequency and intensity of extreme weather events, such as tropical storms and high waves, are anticipated to rise, posing risks to vessels and potentially leading to port closures and disruptions in established shipping routes. Additionally, the melting Arctic ice is opening new shipping lanes, such as the Northern Sea Route, which, while offering faster transit between Europe and Asia, also presents significant navigational and environmental challenges. This article aims to explore these impacts in depth, focusing on how climate change will affect global shipping routes in 2025. Through the analysis of current data and case studies, it seeks to provide insights into the challenges and opportunities faced by the shipping industry in addressing the urgent issue of climate change. A better understanding of these issues is essential for stakeholders to take necessary steps to adapt and mitigate negative impacts on the environment and economy.